LABORATORY EXPERIMENT IN TODAY’S CONDITIONS - Tatarchuk, T. (Sworld-Us Conference proceedings, 2023)
Today, Ukraine faced the problem of organizing education during the war and, accordingly, the problem of full-time education of schoolchildren and students, especially in the southern and eastern regions. In this regard, it is necessary to change the appr